Mechanical Characteristics Of Aluminium 5083 Metal Matrix Strengthen With Fly Ash (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The present work includes the improvement of Hybrid Metal Matrix Composite materials by mixing the attractive qualities of ceramics and metals. Generally, when somewhere around two reinforcement steps are present, it is known as a hybrid composite and this work mainly focuses on representation of these hybrid composite materials. AMMC (Aluminium Metal Matrix Composites) with fly ash particle reinforcements are finding improved applications in aeroplane, automotive and submerged vehicles. In the current work, Aluminium 5083 is utilized as the matrix materials into which fly ash are mixed as the composite material. The consequences of an experimental analysis of the mechanical attributes of combination of fly ash with Al 5083 composites specimens, prepared by stir casting method are described in this work. Five kinds of composite specimens with 45-80% of aluminium 5083 and 20-35% of Fly ash that was kept steady all through was chosen. The mechanical properties calculated were ductility and hardness, compressive strength and tensile strength. The tensile and compressive strength investigation of every specimen for above parameters of load variation and ratio of mixing was found. Morphology of the composite and molecule transmission was researched by scanning electron microscopy.